America's Forgotten Constitutions - ROBERT L. TSAI (Harvard University Press, 2014)
This book was conceived on the day I stumbled upon a copy of John Brown’s Provisional Constitution and Ordinances for the People of the United States. Eagerly, I pored over its contents, wondering why the abolitionist’s imagined community had not gained the same amount of attention as his armed assault on Harpers Ferry. The deeper I delved, the more I realized that the instrument represented the latest in the man’s body of writings having po liti cal and legal signifi cance: letters, op- eds, or gan i za tion al bylaws, a declaration of in de pen dence, and then, fi nally, a proposal for a republican form of government. That discovery led me to wonder what other groups of Americans authored constitutions to rule themselves. The documents I collected revealed a great deal about not only substantive disagreements over law and policy but also ordinary people’s divergent perceptions of po liti cal community and the constitutional pro cess. After investigation and culling, I was left with eight experiments from generative periods in American history. What they tell us about the po liti cal tradition— its tensions, competing forms, and suppressed ideas— became the driving inquiry for this book. Special thanks to librarians and archivists at the Center for Icarian Studies at Western Illinois University, Moorland- Spingarn Research Center Manuscript Division at Howard University, New Hampshire Historical Society, University of Chicago, and University of Nebraska.Billie Jo Kaufman, William Ryan, and the library staff at American University provided invaluable assistance in tracking down primary and secondary materials. The Boston College Law Review offered an early venue to explore John Brown’s constitutional theories.